2020
DOI: 10.1002/adbi.202000034
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Self‐Assembled In Vitro Model to Simulate Direct and Indirect Interactions between Adipocytes and Skeletal Muscle Cells

Abstract: The molecular mechanisms of the development and progression of diabetes and obesity involve complex interactions between adipocytes and skeletal muscle cells. Although 2D in‐vitro models are the gold standard for the mechanistic study of such behaviors, they do not recreate the complexity and dynamics of the interactions between the cell types involved. Alternatively, animal models are used but are expensive, difficult to visualize or analyze, are not completely representative of human physiology or genetic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Several studies have reported the successful 2D coculture of myogenic and adipogenic cells from agriculturally relevant species, [ 429 , 430 , 431 , 432 ] while others have reported small‐scale 3D cultures using human or mouse cells. [ 120 , 428 , 433 ] In addition, the company Ants Innovate is developing a scaffolding system to support the growth of marbled meat containing muscle cells and fat. They have filed a patent on their biomaterial system, [ 434 ] and the founders have recently published an article using a cellulose sponge for organoid culture.…”
Section: Engineering Biological and Structural Complexitymentioning
confidence: 99%
“…Several studies have reported the successful 2D coculture of myogenic and adipogenic cells from agriculturally relevant species, [ 429 , 430 , 431 , 432 ] while others have reported small‐scale 3D cultures using human or mouse cells. [ 120 , 428 , 433 ] In addition, the company Ants Innovate is developing a scaffolding system to support the growth of marbled meat containing muscle cells and fat. They have filed a patent on their biomaterial system, [ 434 ] and the founders have recently published an article using a cellulose sponge for organoid culture.…”
Section: Engineering Biological and Structural Complexitymentioning
confidence: 99%
“…This is particularly true given that skeletal myotubes are characterized by a unique topography represented in their aligned architecture that also imposes a great impact on their function [ 6 ]. More recently, 3D models of the skeletal muscles have also been developed through the employment of extracellular matrix (ECM) gels that could provide the mechanical cues for cells to expand and differentiate into myotubes [ 7 , 8 , 9 ]. However, it is difficult to recapitulate the dynamic conditions in these models including the recapitulation of blood flow and other factors such as mechanical stimuli [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chu et al (2016) [11] reported that porcine pre-adipocyte differentiation was inhibited in a C2C12 co-culture cells and that the expression levels of early differentiation marker genes in adipocytes were lower than those in mono-cultured adipocyte cells. Recently, Shahin-Shamsabadi [12] developed a 3D bio-fabrication method using adipocytes and myoblasts, that analyzed specifically either in direct physical contact or in close proximity such that the paracrine interaction between the cells. The physical contact between cells have been flouted in co-culture systems using transwell inserts and can be used in studies for the development of anti-obesity drugs.…”
Section: Introductionmentioning
confidence: 99%